Maya cultural heritage : how archaeologists and indigenous communities engage the past - McAnany, Patricia Ann (Archaeology in society series., 2016)
"Sheds light on the varied ways today's Maya communities relate to--and are often distanced from--their deep past, historicizes the role of archaeologists and nations in pre-Columbian heritage, and highlights how grass-roots heritage programs can bridge scientific investigation and local community interests"--Provided by publisher